Analysis of The Implementation of Numbered Head Together Strategy In Improving Students’ Reading Comprehension at English Education Department Ganesha University of Education - Juniarta, Putu Adi Krisna (Journal of Education Action Reseach, 2017)
This study aimed at improving the students’ achievement in reading comprehension by using Numbered Head Together Strategy (NHT). The subjects of the study were the students of II B class of English Eduation Department, Undiksha. The study was designed in the form of a classroom action research.Each cycle involved planning, action, observation, and reflection. The data were collected by using tests, diary, and questionnaires. The result of the data showed that the students’ achievement in reading comprehension improved along with the implementation of the NHT strategy. It was shown by the student’s mean score in the tests. In the pre-test the students’ mean score was 53.12 (sufficient). It increased up to 75.15 (very good) in post-test I and it increased to 85.50 (excellent) in post-test II. The result of the questionnaires also indicated that the students gave positive response toward the implementation of the NHT Strategy.